Selenium seed priming enhanced the growth of salt-stressed Brassica rapa L. through improving plant nutrition and the antioxidant system - Hussain, Saber; Ahmed, Shakil; Akram, Waheed; Li, Guihua; Yasin, Nasim Ahmad (Frontiers in Plant Science, 2023)
Various abiotic stresses may affect the germination, growth, and yield of direct-seeded vegetable crops. Seed priming with effective antioxidant mediators may alleviate these environmental stresses by maintaining uniformity in seed germination and improving the subsequent health of developing seedlings. Salt-induced stress has become a limiting factor for the successful cultivation of Brassica rapa L., especially in Southeast Asian countries. The present study was performed to elucidate the efficacy of seed priming using selenium (Se) in mitigating salt-induced oxidative stress in turnip crops by reducing the uptake of Na+. In this study, we administered three different levels of Se (Se-1, 75 μmol L−1; Se-2, 100 μmol L−1; and Se-3, 125 μmol L−1) alone or in combination with NaCl (200 mM). Conspicuously, salinity and Se-2 modulated the expression levels of the antioxidant genes, including catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), and ascorbate peroxidase (APX). The upregulated expression of stress-responsive genes alleviated salt stress by scavenging the higher reactive oxygen species (ROS) level. The stress ameliorative potential of Se (Se-2 = 100 μmol L−1) enhanced the final seed germination percentage, photosynthetic content, and seedling biomass production up to 48%, 56%, and 51%, respectively, under stress. The advantageous effects of Se were attributed to the alleviation of salinity stress through the reduction of the levels of malondialdehyde (MDA), proline, and H2O2. Generally, treatment with Se-2 (100 μmo L−1) was more effective in enhancing the growth attributes of B. rapa compared to Se-1 (75 μmo L−1) and Se-3 (125 μmo L−1) under salt-stressed and non-stressed conditions. The findings of the current study advocate the application of the Se seed priming technique as an economical and eco-friendly approach for salt stress mitigation in crops grown under saline conditions.